Entrepreneurs' Exploratory Perseverance in Learning Settings. (17th December 2015) - Muehlfeld, Katrin; Urbig, Diemo; Weitzel, Utz
Abstract : We introduce "exploratory perseverance" as a novel construct that captures perseverant behavior in settings in which several alternatives can be explored and evaluated. We suggest that entrepreneurs display exploratory perseverance reflected by a tendency to keep exploring broader sets of alternatives, to adopt a parallel rather than sequential approach to trial‐and‐error learning, and, after negative experiences with some alternatives, to be more inclined to give them a second chance. The results from an experimental study of 449 individuals participating in the Iowa Gambling Task indicate that more entrepreneurially experienced individuals display greater exploratory perseverance than those with little to no entrepreneurial experience.